Caracterización de la fibra polimérica para reforzar concreto "Polifibra" de Polyaltec LTDA. (2017)
In this project a mechanical characterization of the polymer fiber to reinforce POLYALTEC LTDA concrete was carried out, which began with the evaluation of the current state of concrete reinforced with fibers. A concrete mix design of 210 kg / 〖cm〗 ^ 3 (21 MPa), composed of ¾ inch gravel, Tolima quarry black sand and Tequendama type cement, which is used for foundations, Plates or Slabs, Columns, Walls, Channels, Tanks and Floors (light traffic). A tensile strength test was performed on the "polyfiber" to characterize the material that will be used as concrete reinforcement. Finally, a comparison was made of the manufacturing cost of a concrete with welded mesh, with reinforced concrete with "poly fiber" to identify the lowest manufacturing cost between the two reinforced concretes.